Image Based Shadowing in Real-Time Augmented Reality - Supan, Peter; Stuppacher, Ines; Haller, Michael (International Journal of Virtual Reality, 2006)
This work presents an approach to render appropriate shadows with Image Based Lighting in Augmented Reality applications. To approximate the result of environment lighting and shadowing, the system uses a dome of shadow casting light sources. The color of each shadow is determined by the area of the environment behind the casting light source. As a result it is possible that changes in the lighting conditions immidiately affect the shadow casting of virtual objects on real objects